The nanoscale characterization and interparticulate interactions of pharmaceutical materials - Hooton, Jennifer Claire (2003)
The aim of this project is to compare pharmaceutical particles made using a Nektar supercritical fluid technology technique called solution enhanced dispersion by supercritical fluids (SEDSTM) to those made using more traditional techniques. This involves a comparison of not only the surface properties of both types of particles, but also the interparticulate interactions. The majority of the work has involved the use of the atomic force microscope (AFM) as both a tool for imaging and for the acquisition of localized force measurements.